4CPS-185 Administration of oral anticancer drugs for patients with swallowing difficulties. (24th March 2020) - Meca, N; Manzaneque, A; Castells, G; Garreta, G; Sebastián, C; Parés, I; Arcenillas, P; Nicolás, J
Abstract : Background and importance: Administration of oral anticancer drugs (OAD) can be problematic in patients with swallowing difficulties. The inability to swallow solid dosage forms can compromise compliance and may lead to poor clinical outcome, representing a challenge for pharmacists. Aim and objectives: To identify alternative administration options for OAD in patients with swallowing difficulties. Material and methods: We conducted a systematic review with paired reviewers. All OAD used in our hospital were included. Our search was made in the following databases: Micromedex, Drug Information Handbook of Oncology and Medline. We also searched in every summary of product characteristics (SPC) and consulted with each laboratory when no information was obtained. Results: Sixty-three active substances were included in the systematic review, 40 were formulated as tablets. In 13 drugs there was information in the drug information document about alternative ways of administration. Information on alternatives in administration was found for 46/63 drugs: 15/46 had a galenic formulation (alectinib/busulfan/cyclophosphamide/erlotinib/etoposide/hydroxycarbamide/imatinib/lapatinib/methotrexate/mitotane/pomalidomide/thalidomide/tetrionine/tioguanine/topotecan); 5/46 had commercially available oral preparations (dabrafenib/dasatinib/eltrombopag/temozolomide/trametinib); 1/46 had both galenic and commercial preparations (mercaptopurine); and 25/46 had an alternative method of manipulation (see table 1 ) following recommendations for manipulation of hazardous drugs (NIOSH, group 1) and providing the necessary material from the pharmacy service. Any alternative was found in 17/63 due to: lack of information (10/17), pharmacokinetics/physicochemical parameters (4/17) and high risk of manipulation (3/17). Unificated OAD recommendations (repeat the process twice to ensure the entire drug). Conclusion and relevance: For most OADs, official information (SPC/laboratory) regarding swallowing difficulties is not available. Therefore, this type of systematic review can be useful for pharmacists to provide an alternative which is equally safe and effective for the patient. References and/or acknowledgements: No conflict of interest.